Factors that Influence the Learning Curve: Evidence from Cost Behavior in Clinical Labs* - Krishnan, Ranjani; Ramasubramanian, Hari (Contemporary Accounting Research, 2023)
ABSTRACT Clinical labs belong to a mature industry and fulfill a critical function in the health‐care value chain. We examine factors that influence the opportunity, motivation, and ability to learn in clinical labs. We hypothesize that with respect to learning about cost: (i) organizational design, such as the extent of outsourcing can impede the opportunity to learn, (ii) quality focus (measured by mortality rates and length of stay (LOS)) can reduce the motivation to learn, and (iii) related task variety (measured by product‐mix breadth) and information technology investments can enhance the ability to learn. Our empirical tests calibrate learning effects on disaggregate (technical and supervisory hours and cost) and aggregate (salary and total direct cost) cost and time pools. Using longitudinal data from clinical labs in California for the period 1997–2015, we find that clinical labs with greater cumulative output have lower average costs, consistent with learning effects in clinical labs. We also find results consistent with our hypotheses about the contextual factors that influence learning rates in clinical labs. Our findings contribute to a better understanding of learning rates with implications for budgeting, forecasting, and performance measurement. The results highlight that learning can be a crucial source of cost reduction in health‐care settings.